Analisis Fragmentasi Hukum Dekarbonisasi Maritim Dan Implementasi Prinsip CBDR Dalam Mewujudkan Keadilan Global - Rahmadani, Putri (Universitas Pancasakti Tegal, 2026)
The decarbonization of maritime transport is a preventive measure to address the climate crisis. However, its implementation remains hindered by the fragmentation of international law and issues of injustice faced by developing countries. This study aims to analyze the regulatory coherence between the 1982 UNCLOS and the technical instruments established by the International Maritime Organization (IMO), as well as to examine the realization of justice through the principle of Common but Differentiated Responsibilities (CBDR). This research employs a normative legal method using statutory and conceptual approaches. The findings reveal legal dualism within the maritime decarbonization regime, in which maritime decarbonization targets and the Net-Zero Emission 2050 agenda remain categorized as soft law, while hard law instruments such as the Energy Efficiency Design Index (EEDI) and the Ship Energy Efficiency Management Plan (SEEMP) are limited to technical aspects and remain ineffective because they primarily apply only to newly built ships. The study identifies structural injustice resulting from the implementation of uniform treatment under the principle of No More Favourable Treatment, without considering the economic and technological disparities of developing countries. Therefore, the integration of legal norms, global financing mechanisms, and technology transfer is necessary to support a just maritime energy transition.